Manufacture of Biodegradable Plastic by Utilizing Palm Oil Empty Fruit Bunch Waste as Cellulose Acetate Synthesis Material: Pembuatan Biodegradable Plastik dengan Pemanfaatan Limbah Tandan Kosong Kelapa Sawit Sebagai Bahan Sintesis Selulosa Asetat - Muhammad Ibrani Aldin; Sergio Privaldio; Febriani Dian Purnama Sari (jurnal makanan tropis dan teknologi agroindustri, 2025)
The fiber content in empty oil palm bunches includes lignin (22.60%), pentosan (25.90%), cellulose (45.80%), and holocellulose (71.88%). The purpose of this study was to utilize empty oil palm bunch waste as a raw material for making cellulose acetate and produce a product in the form of biodegradable plastic by analyzing several test parameters such as tensile strength, elongation and biodegradability. The manufacture of biodegradable plastic uses the solution casting method with the initial step of cellulose synthesis from empty oil palm bunches followed by cellulose acetate synthesis and making biodegradable plastic. The combination of research treatments used was the percentage of glycerol of 3%, 4% and 5% and the percentage of cellulose acetate of 3% and 5%. The results showed that the best treatment obtained based on tensile strength, elongation and biodegradability testing was a sample with a mixture of 3% glycerol and 5% cellulose acetate (G3S5) with a tensile strength value of 2.39 Mpa, elongation of 25.2995% and biodegradability of 69.76% for 7 days.